Vegetarian diets and chronic kidney disease. Issue 2 (5th July 2018) - Chauveau, Philippe; Koppe, Laetitia; Combe, Christian; Lasseur, Catherine; Trolonge, Stanislas; Aparicio, Michel
Abstract: While dietary restriction of protein intake has long been proposed as a possible kidney-protective treatment, the effects of changes in the quality of ingested proteins on the prevalence and risk of progression of chronic kidney disease (CKD) have been scarcely studied; these two aspects are reviewed in the present article. The prevalence of hypertension, type 2 diabetes and metabolic syndrome, which are the main causes of CKD in Western countries, is lower in vegetarian populations. Moreover, there is a negative relationship between several components of plant-based diets and numerous factors related to CKD progression such as uraemic toxins, inflammation, oxidative stress, metabolic acidosis, phosphate load and insulin resistance. In fact, results from different studies seem to confirm a kidney-protective effect of plant-based diets in the primary prevention of CKD and the secondary prevention of CKD progression. Various studies have determined the nutritional safety of plant-based diets in CKD patients, despite the combination of a more or less severe dietary protein restriction. As observed in the healthy population, this dietary pattern is associated with a reduced risk of all-cause mortality in CKD patients. We propose that plant-based diets should be included as part of the clinical recommendations for both the prevention and management of CKD.